PENGEMBANGAN E-MODUL SEJARAH KEMERDEKAAN INDONESIA UNTUK MENANAMKAN RASA CINTA TANAH AIR PADA PESERTA DIDIK KELAS XI DI SMA NEGERI 4 METRO - Dega Ilham Pambudi; Kuswono Kuswono (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The purpose of this study is to describe the history learning media used, obtain the media design of Indonesia's independence history e-module to instill a sense of patriotism, describe the opinions of experts / practitioners whether the design of Indonesia's independence history e-module is appropriate for use or not in class XI in high school Negeri 4 Metro. This study uses a research and development(R&D) method adapted from the Sugiyono Level 1 development model (researching without testing). Stages of research begins with analyzing potentials and problems, then conducts literature studies and information gathering, followed by designing products to obtain product drafts. After producing the draft,the product will be continued to the validation stage by the validator team consisting of material experts and media experts, and a questionnaire will be distributed to students to see their response to the e-module on Indonesia's independence history that was developed.The results of the study are (1) thelearning media used by teachers are still limited to printed books and student worksheets (2) the Indonesian independence history e-module media are designed by adjusting KI and KD in the 2013 curriculum (3) the results of the validation of stage 1 material experts are 80%